BIOLEACHING UNTUK MENINGKATKAN PRODUKTIVITAS LAHAN SULFAT MASAM AKTUAL UNTUK TANAMAN PADI - Maftu’ah, Eni; Susilawati, Ani (Research Center for Biology-Indonesian Institute of Sciences, 2018)
Technology of microbial utilization to accelerate the oxidation of pyrite followed by leaching (bioleaching) has the potential to resolve problems in land management of actual acid sulphate soil. The research aims to obtain a bioleaching technology package that can improve the productivity of the actual acid sulfate soil. The experiment was conducted on tidal swamp land that has soil type of actual acid sulfate at Wana Raya sub-district, district Batola, South Kalimantan, in July - November, 2014. The study was designed by using strip plot with three replications. The treatment consisted of two factors, namely application of an oxidizing microbial pyrite and leaching amount (intensity). The main plot consisted of (P0) without leacing (naturally), (P1) six times leaching , (P2) eight times leaching, and (P3) 12 times leaching. Subplot consisted of (M0) without oxidizing microbial pyrite, (M1) with oxidizing microbial plant used in this study is Inpara 3 of rice variety. Observations were made on soil pH, oxidizing bacteria pyrite, growth of rice plants (plant height and number of tillers) and rice yield. The results showed that the main problem of actual acid sulfate land studied is a high soil acidity (pH of 3.44). Influ-ence of leaching was greater than microbial application on crop yields. Application of the pyrite oxidizing bacterial and leaching eight times gave the best influence on the growth and yield of rice plants.